2020
DOI: 10.1177/1073191120983919
|View full text |Cite
|
Sign up to set email alerts
|

A Known-Groups Validation of the Medical Symptom Validity Test and Analysis of the Genuine Memory Impairment Profile

Abstract: This study cross-validated the Medical Symptom Validity Test (MSVT) in a mixed neuropsychiatric sample and examined its accuracy for identifying invalid neuropsychological performance using a known-groups design. Cross-sectional data from 129 clinical patients who completed the MSVT were examined. Validity groups were established using six, independent criterion performance validity tests, which yielded 98 patients in the valid group and 31 in the invalid group. All MSVT subtest scores were significantly lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…We established each participant's validity group membership on the basis of five independent criterion PVTs: Dot Counting Test (DCT; Boone et al, 2002; sample failure rate: 17.5%); Medical Symptom Validity Test (MSVT; Green, 2004;Resch et al, 2022; sample failure rate: 19.3%; using the genuine memory impairment profile when appropriate); Reliable Digit Span (RDS; Schroeder et al, 2012;Wechsler, 2008; sample failure rate: 12.6%); Test of Memory Malingering (TOMM Trial 1; Denning, 2012;Tombaugh, 1996; sample failure rate: 22.4%); and Word Choice Test (WCT; Bernstein et al, 2021;Neale et al, 2022;Pearson, 2009; sample failure rate: 14.8%). Specifically, patients with ≤1 criterion PVT failure were classified into the valid group (n = 177; 79.4%), whereas those with ≥2 criterion PVT failures constituted the invalid group (n = 46; 20.6%), consistent with current practice standards and past empirical findings regarding these measures (Jennette et al, 2021;Rhoads et al, 2021).…”
Section: Participantsmentioning
confidence: 99%
“…We established each participant's validity group membership on the basis of five independent criterion PVTs: Dot Counting Test (DCT; Boone et al, 2002; sample failure rate: 17.5%); Medical Symptom Validity Test (MSVT; Green, 2004;Resch et al, 2022; sample failure rate: 19.3%; using the genuine memory impairment profile when appropriate); Reliable Digit Span (RDS; Schroeder et al, 2012;Wechsler, 2008; sample failure rate: 12.6%); Test of Memory Malingering (TOMM Trial 1; Denning, 2012;Tombaugh, 1996; sample failure rate: 22.4%); and Word Choice Test (WCT; Bernstein et al, 2021;Neale et al, 2022;Pearson, 2009; sample failure rate: 14.8%). Specifically, patients with ≤1 criterion PVT failure were classified into the valid group (n = 177; 79.4%), whereas those with ≥2 criterion PVT failures constituted the invalid group (n = 46; 20.6%), consistent with current practice standards and past empirical findings regarding these measures (Jennette et al, 2021;Rhoads et al, 2021).…”
Section: Participantsmentioning
confidence: 99%
“…This battery included the Test of Premorbid Function (TOPF; Pearson, 2009), Verbal Fluency (F/A/S and Animal Naming; Heaton et al, 2004), Rey Auditory Verbal Learning Test (RAVLT; Schmidt, 1996), Brief Visuospatial Memory Test-Revised (BVMT-R; Benedict, 1997), Wechsler Adult Intelligence Scale-Fourth Edition (WAIS-IV; Wechsler, 2008) Processing Speed Intext (PSI), Trail Making Test (TMT; Heaton et al, 2004), and Stroop Color and Word Test (Golden, 1978). Of note, FSIQ 100.18 (9.20) 77-128 100.83 (8.82) 77-128 97.51 (10.46) 79-115 3 although embedded PVTs derived from the RAVLT (Boone et al, 2005;Pliskin et al, 2021;Soble et al, 2021a) and BVMT-R (Bailey et al, 2018;Resch et al, 2022b), Verbal Fluency, TMT, and Stroop (Khan et al, 2022;White et al, 2020) have been identified; these embedded indicators were not included in the reference standard in order to avoid criterion contamination by keeping the neurocognitive tests fully independent from the criterion PVTs used to establish the validity groups. Among the 30 total patients who were actively compensation-seeking at the time of evaluation (see Table 1), 27% (8/30) obtained ≥ 2 PVT failures and were classified into the invalid group, whereas the remaining 73% (22/30) of those who were actively compensationseeking demonstrated valid test performance (i.e., ≤ 1 PVT failure).…”
Section: Neuropsychological Test Batterymentioning
confidence: 99%